Accessing the rich carbon nitride materials chemistry by heat treatments of ammonium thiocyanate, NH4SCN. Issue 4 (19th June 2019) - Larsen, Finn Krebs; Hasen Mamakhel, Aref; Overgaard, Jacob; Jørgensen, Jens-Erik; Kato, Kenichi; Brummerstedt Iversen, Bo
Abstract : Carbon nitrides include functional materials and a range of carbon nitride products obtained from the pyrolysis of NH4 SCN is presented here. Abstract : Carbon nitride materials include functional materials, and their chemical diversity and complexity are becoming increasingly appreciated. Heating of NH4 SCN leads to a range of new carbon nitride compounds, which have been structurally characterized by single‐crystal X‐ray diffraction. Heating at ambient pressure to 175°C leads to guanidinium thiocyanate, H6 CN3 SCN (1 ), and when maintaining that temperature for about 12 h a water‐insoluble carbon nitride product is formed, which is a co‐crystal between melamine and melamium thiocyanate, [H6 C3 N6 ]·[H10 C6 N11 ] + ·[SCN] − (2 ). In situ powder X‐ray diffraction measurements of this material reveal a gradual transformation from (2 ), via two intermediate products, to a final melon‐like end product. The first of these forms between 350 and 400°C, and is an adduct of melam and melamium thiocyanate, [H9 C6 N11 ]·2[H10 C6 N11 ] + ·2[SCN] − (3 ). The second forms between 400 and 480°C, and is identified as melem, 2, 5, 8‐triamino‐tri‐ s ‐triazine, H6 C6 N10 (4 ). On heating of (2 ) in a sealed ampoule to 600°C, various crystals were obtained and six crystal structures were determined from the batch: 1, 3, 5‐triazine‐2, 4, 6‐triamino, H6 C3 N6 (5 ), 1, 3, 5‐triazine‐2, 4‐diamino, H5 C3 N5 (6 ), 1, 1′, 3, 3′, 5, 5′‐triazine‐2, 2′, 4, 4′‐tetraamino, H8 C6 N10 (7 ), 2[H6 C3 N6 ]·[H10 C6 N11 ] + ·[SCN] − (8 ) and 2[H6 C3 N6 ]·[H7 C3 N6 ] + ·[SCN] − (9 ). Finally, a recrystallized decomposition product was found to be [H6 C3 N6 ]·[H7 C3 N6 ] + ·[SCN] − ·[H2 O] (10 ).